Applying the behavior change wheel to identify pandemic-related attitudes and feelings about physical activity as predictors of physical activity level among university students in Indonesia during the COVID-19 pandemic - Wibowo, Rakhmat Ari; Sofyana, Meida; Agustiningsih, Denny (Frontiers in Education, 2022)
A recent systematic review found a significant drop in physical activity (PA) among university students during the coronavirus disease 2019 (COVID-19) pandemic. Identifying students’ attitudes and feelings about PA and coronavirus, which could facilitate or hinder PA, is essential to guide intervention planning. Therefore, this study aimed to examine attitudes and feelings about PA and coronavirus as predictors of PA levels. We conducted a cross-sectional study among undergraduate university students in Indonesia to collect their PA levels using the global PA questionnaire version 2 and their attitudes and feelings about PA in pandemic situations. A binomial logistic regression has been conducted to predict whether students will sufficiently engage in PA based on their attitudes and feelings related to PA, coronavirus, and demographic characteristics. Results from 588 undergraduate students (75% female) showed that students perceived the health benefits of PA, perceived feeling guilty about wanting to do PA during the pandemic, body mass index (BMI), and field of study were statistically significant predictors of PA levels. An increase of one unit of perceived health benefits of PA increases the odds of meeting the PA guidelines by 2.313 (95% confidence interval 1.708–3.132, p < 0.001). On the other hand, raising one point of feeling guilty about conducting PA was associated with 1.285 times lower odds (95% confidence interval 1.062–1.558, p = 0.01) of meeting the PA guidelines. Thus, intervention should increase students’ awareness of the physical health benefits of PA during the pandemic and reduce their feeling of guilty about conducting the PA.